External equivalents for safety analysis of interconnected electrical systems - Paucar, V. Leonardo (2002)
In the planning, operation and control of electric power systems as well as in the electric marketsanalysis, some large portions of the electrical networks may be represented by reduced equivalents, thus diminishing the problem's size and easing the computational processing, such as power flow, short circuit analysis, economic dispatch, transient stability, among others,that are routinely performed at the control centers. In this paper are presented the main methods for determining the external equivalents used mainly in the security analysis of interconnected power systems. Are also included the results of security analysis using external equivalentsapplied to the Ward-Hale 6-bus test system, and other application using data of a real system corresponding to a configuration of 313 buses of the interconnected national Peruvian power system (SEIN).